Job-Hopping Intention Among Lecturers in Private Education Institutions - Mat Zaki, Muhammad Ridhwan; Ma’amor, Hairunnisa; Munir, Ros Intan Safinas; Mohamad Nazri, Nur Zarifah (Information Management and Business Review, 2024)
The practice of frequently changing jobs known as job-hopping is increasingly prevalent across industries, including academia in search of better opportunities or personal growth. Due to this situation, it is more challenging for educational institutions, particularly in the private education sector to retain highly skilled lecturers in the organization. This study aims to identify the relationship between job-hopping intention among lecturers in private educational institutions and the factors that are job satisfaction, job motivation, psychological contract, and person-environment fit. Data was collected from 260 respondents across all KPTM branches through questionnaires and analyzed using SPSS version 29. The findings show that strong psychological contract negatively influences job-hopping. On the other hand, job satisfaction, job motivation, and person-environment fit show no significant influence. This study not only provides a deeper understanding of job-hopping motivation but also gives valuable insight for policymakers to develop strategies and modules that enhance job satisfaction and retention among lecturers, especially in private education institutions.